Efficacy and anti-inflammatory properties of low-molecular-weight fucoidan in patients with atopic dermatitis: a randomized double-blinded placebo-controlled trial - Huei-Ling Shih; Pin-Han Wang; I-Hsin Shih; Sindy Hu; Jr-Rung Lin; Pei-Yu Hsu; Sien-Hung Yang (International Journal of Food Properties)
Atopic dermatitis (AD) is a chronic recurrent inflammatory skin disease. Fucoidans are reportedly effective in treating AD; however, their clinical efficacy requires further exploration. This study aimed to investigate the clinical efficacy of low-molecular-weight fucoidan (LMF) supplementation in patients with AD and reveal the underlying mechanism of its effects; this is a randomized, double-blind, placebo-controlled trial. Participants were randomly assigned to a study or control group to receive conventional AD therapy with oral supplementation of either LMF or placebo for 12 weeks. Symptom severity was measured by the SCORing Atopic Dermatitis (SCORAD) index. Each participant used a diary to record daily medication use. Blood samples were collected at three time points for assessing AD-related cytokines, immunoglobulin E (IgE), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), white blood cell (WBC) count, the percentage of eosinophils, and biochemical profiles of hepatic and renal functions. The study group showed significant symptom relief, whereas the control group showed no significant improvements. The frequency of steroid ointment application significantly decreased, and the frequency of oral antihistamine use decreased in the study group, whereas no significant changes were observed in the control group. The AD-related immune parameters serum IgE, eosinophils, CD8+ T cells, interferon-γ (IFN-γ), ESR, and CRP significantly decreased in the study group but not the control group. There were no severe adverse events in either group. This study is the first to demonstrate the effectiveness and safety of LMF as a supplemental therapy for patients with AD via its anti-inflammatory activity.